DEBYE-WALLER TYPE EXPRESSIONS FOR THE NUCLEAR ELASTIC FORM FACTORS AT SMALL MOMENTUM TRANSFERS - Grypeos, M. E.; Lalazissis, G. A.; Massen, S. E.; Panos, C. P. (HNPS Advances in Nuclear Physics, 2020)
The problem of the estimate of the nuclear elastic form factors in Born approximation is discussed in the region of small momentum transfers q. It is shown that approximate expressions of the Debye-Waller type are suitable for estimates of these form-factors in the oscillator shell model, for sufficiently small q.